Fully convolutional networks in multimodal nonlinear microscopy images for automated detection of head and neck carcinoma: Pilot study - Rodner, Erik; Bocklitz, Thomas; Von Eggeling, Ferdinand; Ernst, Guenther; Chernavskaia, Olga; Popp, Jürgen; Denzler, Joachim; Guntinas-Lichius, Orlando (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2019)
Background: A fully convolutional neural networks (FCN)-based automated image analysis algorithm to discriminate between head and neck cancer and noncancerous epithelium based on nonlinear microscopic images was developed. Methods: Head and neck cancer sections were used for standard histopathology and co-registered with multimodal images from the same sections using the combination of coherent anti-Stokes Raman scattering, two-photon excited fluorescence, and second harmonic generation microscopy. The images analyzed with semantic segmentation using a FCN for four classes: cancer, normal epithelium, background, and other tissue types. Results: A total of 114 images of 12 patients were analyzed. Using a patch score aggregation, the average recognition rate and an overall recognition rate or the four classes were 88.9% and 86.7%, respectively. A total of 113 seconds were needed to process a whole-slice image in the dataset. Conclusion: Multimodal nonlinear microscopy in combination with automated image analysis using FCN seems to be a promising technique for objective differentiation between head and neck cancer and noncancerous epithelium.
CRIS-Team Scopus Importer:2023-04-20
Keywords: coherent anti-stokes Raman scattering; convolutional neural networks; diagnostics; digital pathology; head and neck cancer; image analysis; second-harmonic generation; semantic segmentation; spectral histopathology; two-photon excited fluorescence